2010
DOI: 10.1016/j.ophtha.2009.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Validation of Quality-of-Life Questionnaires for Intermittent Exotropia

Abstract: Purpose We report the development and initial validation of patient–derived, health related quality of life (HRQOL) questionnaires for intermittent exotropia (IXT). Design Cross-sectional study Participants In a development phase, 27 children (aged 2–17 years) with IXT and one of their parents. In an initial validation phase, 33 children with IXT and 49 control children (aged 5–17 years) along with one parent for each child. Children in the control group had no strabismus or amblyopia. Methods Individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 19 publications
1
104
0
3
Order By: Relevance
“…In this scenario, however, such an approach may result in measures that capture (in addition or solely) parental stress and impact on the family (eg, NLDO76–79). One instrument that we identified (IXTQ48 50) provides an example of how the assessment of parental anxieties and QoL can be helpfully separated from the child's with concurrent development of two complementary but distinct, respondent-targeted measures.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, however, such an approach may result in measures that capture (in addition or solely) parental stress and impact on the family (eg, NLDO76–79). One instrument that we identified (IXTQ48 50) provides an example of how the assessment of parental anxieties and QoL can be helpfully separated from the child's with concurrent development of two complementary but distinct, respondent-targeted measures.…”
Section: Discussionmentioning
confidence: 99%
“…The Intermittent Exotropia Questionnaire (IXTQ) is a condition-specific, patient-derived validated HRQOL questionnaire for children with IXT and their parents 9. Although other questionnaires, for example, VF-14 and PedsQL, have also been used to assess HRQOL in children with strabismus, they are not specific to IXT 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…Carlton et al 8 identified four strabismus-and amblyopia-specific QoL questionnaires: the amblyopia and strabismus questionnaire 46 (A&SQ), the amblyopia treatment index, 11 the adult strabismus questionnaire [19][20], and the intermittent exotropia questionnaire. 22 The two strabismusspecific questionnaires, the A&SQ and AS-20, have both been shown to have better discriminatory ability when compared with the SF-12 and VFQ-25 18,46 for those with strabismus.…”
mentioning
confidence: 99%